Mechanical interaction within badminton forehand shot technique: a review paper - Syazwan Ramli, Alif Syamim; Tengku Kamalden, Tengku Fadilah; Sharir, Raihana; Harith, Hazreen Haizi; Hanafi, Marsyita; Gasibat, Qais; Samsudin, Shamsulariffin (Australian International Academic Centre, 2021)
Background: The performance outcome model in qualitative technique analysis can determine the mechanical interactions between a performance outcome and the factors that yield such results in sports techniques. Very little attention has been received for badminton forehand shots for such model work, considering the significance of this technical skill as fundamental to play badminton and as important offensive shots. Objective: This study proposes a performance outcome model that associates performance criteria and relevant mechanical variables in the badminton forehand shot technique. Methods: Literature review provided the basis of model development. The Literature research in this paper was conducted in the following databases; PubMed, ScienceDirect, Google Scholar Medline, Pedro, and Cinahl. An additional search (including relevant grey literature) was also done on the internet through ResearchGate. Relevant literature research related to the keywords such as biomechanics of badminton, badminton forehand shot, biomechanical analysis, badminton performance, racquet sports, performance indicators, technique analysis and technique models were included and reviewed. Results: The results managed to present a synthesis of the literature review and provided constructive discussions as a basis to propose a performance outcome model that illustrates mechanical interactions that contribute to badminton forehand and shot technique performance. Conclusions: This model manages to find mechanical relationships and allows for a better grasp of understanding the association between performance criteria and mechanics in the badminton forehand shot technique, which is bases on the kinetic chain principle through the body segmental coordination.